Being there: scientific saturation and technical diving with in situ instrumentation in an internal surf zone reveal driving physical dynamics of coral reefs - Leichter, James J.; Wing, Stephen R.; Stokes, M. Dale; Genovese, Salvatore J. (Frontiers in Marine Science, 2025)
Since the advent of recreational and scientific SCUBA diving in the 1950s, coral reefs have become one of the most studied and appreciated marine ecosystems. Direct human observations have been essential to many scientific discoveries. However, most in-water experiences are limited to short durations (tens of minutes to ~1 hour), shallow depths (surface to ~30 m), and calm sea conditions, leaving much of the reef environment underexplored—particularly deeper zones (to ~80 m) and with periods of challenging environmental conditions undersampled. Over a 20-year period, we employed research approaches centered on extended human observation through advanced modes of scientific diving, combined with in situ instrumentation. These efforts revealed extensive heterogeneity in reef physical conditions driven by internal waves, varying across time (minutes to seasons) and space (meters to 100s of km). Technological advances in autonomous sensors, microprocessors, and memory allowed for continuous, distributed, and high-resolution environmental sampling and 3D data visualization over time. Our work was enabled by enriched oxygen (nitrox) and helium-oxygen (trimix) technical diving, as well as saturation diving supported by the U.S. National Undersea Research Center and Aquarius Reef Base in the Florida Keys. Early direct observations of rapid changes in temperature, salinity, and current flow—and associated behavioral responses of reef organisms—led to new understanding of internal wave dynamics, including the formation of bores or “internal surf,” as persistent features of reef environments. These observations prompted further studies into nutrient and plankton transport, and revealed trophic connections between shallow reefs and deeper macroalgal communities (~50–80 m). Targeted deployments of high-resolution instruments helped characterize small-scale variability and link local dynamics to regional internal wave forcing by the Florida Current. A late season tropical cyclone arriving during a saturation diving mission in 1994 further highlighted extreme reef environmental dynamics rarely observed directly by humans. Together, these findings show how direct human observations, combined with continuous environmental monitoring, are essential for understanding complex reef processes—offering insights into ecosystem connectivity and coral thermal refugia under climate change.